Evaluating the impact of the biocontrol agent Trichoderma harzianum ITEM 3636 on indigenous microbial communities from field soils - Ganuza, Mauricio Roque (2018)
Aim: to investigate the impact of inoculating peanut seeds with the biocontrol agent Trichoderma harzianum ITEM 3636 on the structure of bacterial and fungal communities from agricultural soils. Methods and Results: PCR‐Denaturing gradient gel electrophoresis (PCR‐DGGE) and next‐generation sequencing (NGS) of amplicons (or marker gene amplification metagenomics) were performed to investigate potential changes in the structure of microbial communities from fields located in a peanut‐producing area in the province of Córdoba, Argentina. Fields had history of peanut smut (caused by Thecaphora frezii) incidence. The Shannon indexes (H’), which estimate diversity, obtained from the PCR‐DGGE assays did not show significant differences neither for bacterial nor for fungal communities between control and inoculation treatments. On the other hand, the number of Operational Taxonomic Units (OTUs) obtained after NGS was similar between all the analyzed samples. Moreover, results of alpha and beta diversity showed that there were no significant variations between the relative abundances of the most representative bacterial and fungal phyla and genera, in both fields. Conclusions: T. harzianum ITEM 3636 decreases the incidence and severity of agriculturally relevant diseases without causing significant changes in the microbial communities of agricultural soils.